Modulate hypercholesterolemia as a metabolic disturbance induced oxidative stress injury by functional effects of some mix plant seeds in experimental rats - Mahmoud, Nabila (Journal of medical and pharmaceutical sciences, 2018)
The moderated effect of flax, sunflower and pumpkin seeds are common used as edible seeds in human nutrition. The study focused on flax/sunflower/pumpkin seeds mix powder on rat suffered from hypercholesterolemia. The feed intake, body weight gain, feed efficiency ratio, relative liver and heart weight, lipid profile, liver enzymes, kidney function, oxidative stress markers, lipid peroxide levels and heart histopathology for normal and hypercholesterolemic rats were examined. Main first group (6 rats) was fed on basal diet for 12 weeks. Main second group (24 rats) fed on diet with hypercholesterolemia for 8 weeks, then diet supplemented with mix seeds powder 3, 6 and 9%, respectively for successive 4 weeks. The results clearly demonstrate that dietary treatment with mix flax /sunflower /pumpkin seeds (30 g; 60 g and 90 g) for 4 weeks has a powerful modulating effect to improve biological evaluation, serum blood levels and heart tissues changes of hypercholesterolemic rats then, this mix seeds have the potential in reducing cardiovascular diseases complications due to hypercholesterolemia.